Research trends in fear of missing out (FOMO) and mental health: A bibliometric analysis (2016-2026) - Sakarji, Siti Rosnita; Abdullah Thani, Ayu Kamareenna; Aminuddin, Azwan Shah; Amran, Atiela; Azhari, Nurul Nadhira Amalin (Journal of Islamic, Social, Economics and Development, 2026)
Fear of Missing Out, or FoMO, has become an emerging topic in academic circles, especially because of its strong ties to social media and its negative impact on mental health. Even though there has been a surge in research on this subject, it still lacks a thorough overview of the global research landscape, collaboration patterns, and the key themes surrounding FoMO and mental health. Therefore, this bibliometric analysis focuses on the growth of publications, international collaborations, and the main research themes. A total of 79 documents sourced from the Scopus database were identified and published between 2016 and 2026 using a structured screening process. VOSviewer was utilized to examine publication trends, co-authorship networks among countries, and patterns of keyword co-occurrence. The results show consistent and significant rise in publications about FoMO and mental health during the study period, indicating a growing academic interest in this area. The co-authorship analysis across 50 countries revealed 16 nations that met the minimum publication threshold, showcasing active international collaboration. The United States, China, India, Canada, and the United Kingdom stood out as key contributors. The keyword co-occurrence analysis identified 55 high-frequency keywords, which were organized into three main clusters, with “fear of missing out” being the most prominent term. Other notable keywords included social media, anxiety, depression, addiction, adolescent, adult, psychology, and young adult, underscoring the close relationship between FoMO, social media usage, addictive behaviours, and mental health outcomes. The findings highlight the pivotal role of social media use and addiction in shaping FoMO experiences and psychological health, while also revealing some gaps in methodology and geography within the literature.